Heirs, kin, and creditors in Renaissance Florence / Thomas Kuehn. - Kuehn, Thomas, 1950- (Cambridge University Press, 2008)
This study, based on Florentine repudiations of inheritance, reveals that inheritance was not simply an automatic process where the recipients were passive, if grateful. In influential European societies of the past, it was in fact a process that continued long after the deceased's death. Heirs also had options: at the least, to reject a burdensome patrimony, but also to manoeuvre property to others and to avoid (at times deceptively, if not fraudulently) the claims of others to portions of the estate. Repudiation was a vestige of Roman law that once again became a viable legal institution with the revival of Roman law in the Middle Ages. Florentines incorporated repudiation into their strategies of adjustment after death, showing that they were not merely passive recipients of what came their way. Further, these strategies fostered family goals, including continuity across the generations.